Discovery of Dual Inhibitors of Acetyl and Butrylcholinesterase and Antiproliferative Activity of 1, 2, 4‐Triazole‐3‐thiol: Synthesis and In Silico Molecular Study. Issue 21 (5th June 2020) - Siddiqui, Sabahat Zahra; Arfan, Muhammad; Abbasi, Muhammad Athar; Aziz‐ur‐Rehman,; Shah, Syed Adnan Ali; Ashraf, Muhammad; Hussain, Safdar; Saleem, Rehman Shah Zaib; Rafique, Rafaila; Khan, Khalid Mohammed
Abstract: The aim of this current study is to discover effective acetyl and butrylcholinesterase enzyme inhibitors. A concise library of S ‐alkylated/arylated‐4‐ethyl‐5‐(4‐methoxyphenyl)‐4 H ‐1, 2, 4‐triazole‐3‐thiols 5–18 was synthesized by using a multistep reaction sequence. The compounds were characterized by using a combination of several spectroscopic techniques including FT‐IR, 1 H‐NMR, 13 C‐NMR and EI‐MS. All derivatives 5–18 were tested for in vitro AChE and BChE inhibitory activity. It is worth mentioning that all synthetic compounds exhibited moderate inhibition judged by the potency of action, that is inhibition in the range of 45.87 ± 0.92 ‐ 435.15 ± 1.69 μ M for AChE, and 3.27 ± 0.81 ‐ 346.25 ± 1.36 μ M for BChE. Anti‐proliferative activity results suggested that the derivative with longest alkyl‐chains at S ‐atom of the triazole moiety was most potent with 4.91% cell viability at 25 μ M and 2.97% cell viability at 50 μ M and showed selectivity of inhibition of BChE over AChE at the tested concentrations providing a hit for subsequent structure optimization. Lastly, the in silico studies were performed to ascertain the binding interactions of compound with the active site of enzymes. Abstract : S ‐Alkylated/arylated‐4‐ethyl‐5‐(4‐methoxyphenyl)‐4 H ‐1, 2, 4‐triazole‐3‐thiols were synthesized by multistep reaction. 4‐Methoxybenzohydrazide and ethyl isothiocyanate were reacted in methanol to afford an intermediate N‐ ethyl‐2‐(4‐methoxybenzoyl)hydrazinecarbothioamide which undergoes cyclization in aqueous alkaline media; 10% NaOH to yield 4‐ethyl‐5‐(4‐methoxyphenyl)‐4 H ‐1, 2, 4‐triazole‐3‐thiol as parent compound which further react with alkylhalides in N, N ‐dimethylformamide in the presence of LiH as catalyst. Synthesized compounds were tested for their possible acetyl/butrylcholinesterase enzymes inhibition.